Pengaruh Struktur Modal, Profitabilitas, StrukturBiaya Dan Kepemilikan Institusional Terhadap Nilai Perusahaan - Rizkiastuti, Adiek Iriani, Drs. Suyatmin Waskito Adi, M.Si (2016)
Company as an economic entity has a goal in operating its business operation.The company goal as general is divided into two companies that are short time goal and long time goal.The company short time goal is resulting profit for the company is maximalizing the value of company,with the result that as high the company value so that the owner will be more prosperous. So the company value for the investor and creditor is so important to be known. This study aimed to analizing the effect of Capital Structure, Profitability, Cost Structure and Institution Ownership of the enterprise value of the property, real estate dan building constructions companies listed in Indonesia Stock Exchange. The population used in this study are all property, real estate dan building constructions companies listed in Indonesia Stock Exchange during the period 2012-2014. Sampling method by purposive sampling according to criteria that have been determined. The number of samples collected as many as 194 companies, as there are data outliers as many as 52 companies then sampled to 75 companies. Data analysis technique uses ltipleregression analysis. The results showed that simultaneously all independent variables in this study significantly influence the value of the company. In partial results of this study indicate that profitability significantly affect the value of the company, while funding decisions does not significantly affect the value of the company.